Ternary Intermetallic Formation And Mechanical Strength Of Wave Soldered BGA Joints - Leong, Kum Foo (2003)
The densification of the input/output in integrated circuits necessitates a transition from the through-hole assembly to the surface mount technology. The wave soldering process for the through-hole assembly is incorporated to form a mixed-soldering process for SMT to ensure mechanical strength in some of the peripherals. In this project, the effect of repeated wave-soldering heating on the SMT mounted Sn/Pb eutectic solder joint on HASL (Hot Air Solder Leveling) PCB is investigated by measuring its three point bend strength.